2012
DOI: 10.1038/ejcn.2012.35
|View full text |Cite
|
Sign up to set email alerts
|

MRI-measured pelvic bone marrow adipose tissue is inversely related to DXA-measured bone mineral in younger and older adults

Abstract: Background/ObjectiveRecent research has shown an inverse relationship between bone marrow adipose tissue (BMAT) and bone mineral density (BMD). There is a lack of evidence at the macro-imaging level to establish whether increased BMAT is a cause or effect of bone loss. This cross-sectional study compared the BMAT and BMD relationship between a younger adult group at or approaching peak bone mass (PBM) (age 18.0-39.9 yrs) and an older group with potential bone loss (PoBL) (age 40.0-88 yrs).Subjects/MethodsPelvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 48 publications
5
84
1
Order By: Relevance
“…Age-related osteoporosis is characterized by reduced bone formation and increased marrow fat accumulation (3)(4)(5)(6). This age-related reduction in osteoblast activity is partly caused by the fact that BMSCs from elderly subjects have reduced capacity to differentiate into osteoblasts and increased capacity to differentiate into adipocytes (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Age-related osteoporosis is characterized by reduced bone formation and increased marrow fat accumulation (3)(4)(5)(6). This age-related reduction in osteoblast activity is partly caused by the fact that BMSCs from elderly subjects have reduced capacity to differentiate into osteoblasts and increased capacity to differentiate into adipocytes (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…This finding corroborates previous studies that found lower unsaturation in osteoporosis and in diabetes, both of which involve elevated fracture risk, (5,12) but contrasts with studies that have shown an inverse relationship between the quantity of marrow fat and BMD or bone mass. (3,9,10,13) Additionally, this finding raises the issue of causality-does marrow fat become less unsaturated before a fracture, or afterward? Does altered metabolism in diabetes change marrow lipid composition and thereby increase skeletal fragility?…”
mentioning
confidence: 99%
“…In healthy children and adults, a reciprocal relationship has been described between marrow adiposity and bone parameters at both axial and appendicular skeleton [81][82][83][84]. Misra and colleagues have shown, using magnetic resonance spectroscopy techniques, that adults with AN have increased marrow fat compared to normal-weight controls, and that marrow fat is inversely associated with areal bone density measures [85].…”
Section: Introductionmentioning
confidence: 99%